USING PROBABILITY REGRESSION MODELS TO MEASURING MANAGEMENT EFFICIENCY FOR BROILER PROJECTS - & Faeq, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The efficiency of management is determining factor for the success or failure of agricultural projects generally and Livestock particularly achieving its objectives. Therefore, this research came to diagnose the most important variables that determine the efficiency of management using the probability regression models to measure the probability of management efficient of broilers production projects using  random sample included (60) broilers projects represented 11.6% of Baghdad province (research community) in 2016. After estimating the relationship between the management efficiency (descriptive dependent variable) and the independent variables affecting it (age, educational level, production index (PI), experience). The results showed that the parameters of these variables were positive according the economic logic, except for the parameter of the experience variable, which was negative contrary to economic logic. The results showed that the independent variables were significant at 1% and 5% levels in logit and probit models, except the PI variable, which was insignificant in the Tobit model. By comparing the results of the three models and the tests performed, the probit model showed its preference.  The age and educational level were most important independent variables affecting the efficiency of management, the suggested recommendations of the research indicated to increase the efficiency of the administration through training courses to train workers and teach them to follow the modern methods in poultry production and raise the scientific methods because of its impact in increasing productivity.